Pengaruh Perilaku Warga Terhadap Volume Sampah di Bandung - Pratiwi Pratiwi; Candra Setya Nugroho (Puslatbang KHAN, 2016)
Globally, Indonesia still faces of the millennium development goals (MDG) challenges especially in ecological waste management. Then it is necessary to accelerate the innovation of government waste management performance and reduce the volume of waste. This research was focused at Coblong District, Bandung City and employed quantitative descriptive method. The method was used to describe the influence of people's behavior to the volume of waste that is produced. This research also recommends innovation on waste management model. This study shows that there is significant influence between the behavior of citizens and the volume of waste generated. Therefore, innovation model of independent waste management by the residents is very effective and efficient especially with the assistance of relevant NGOs. This research also recommends that it is necessary to create more impactful waste management by promoting citizen participation and more intense assistance from the Government and NGOs in the District Coblong Bandung.